Unconventional petroleum geology - Zou, Caineng, 1963- (Elsevier, 2013)
Advances in hydrocarbon technology and petroleum development systems have recently made the exploration of unconventional hydrocarbons, such as shale gas, tight sandstone oil and gas, heavy oil, tar sand, and coalbed methane, the hottest trend in the petroleum industry. However, conventional exploration and recovery methods do not lend themselves to unconventional sources of hydrocarbons, so you need a thoroughly detailed yet accessible reference to help you understand this newest of exploration methods. Unconventional Petroleum Geology is the first book its kind to collectively identify, catalog, and assess the exploration and recovery potential of the Earth's unconventional hydrocarbons. Detailed case studies from around the world act as real-world application templates, helping you make the book's concepts immediately practical and useful in the field. Provides you with a detailed assessment of the exploration and recovery potential of the full range of unconventional hydrocarbons. The logical and intuitive three-part approach of systematically identifying an unconventional hydrocarbon, cataloguing its accumulation features, and assessing its exploration and recovery potential can assist you in immediately implementing this approach in the field-anywhere in world. MoreMore than 300 illustrations-many in full color-capture the detailed intricacies and associated technological advances in unconventional hydrocarbon exploration and will help you retain key concepts More than 20 case studies and examples from around the world conclude each chapter and will aid you in the application of key exploration and recovery techniques.